2007
DOI: 10.1007/s10021-007-9074-3
|View full text |Cite
|
Sign up to set email alerts
|

Plant Spatial Pattern Predicts Hillslope Runoff and Erosion in a Semiarid Mediterranean Landscape

Abstract: The importance of the spatial pattern of vegetation for hydrological behavior in semiarid environments is widely acknowledged. However, there is little empirical work testing the hypothetical covariation between vegetation spatial structure and hillslope water and sediment fluxes. We evaluated the relationships between vegetation structural attributes (spatial pattern, functional diversity), soil surface properties (crust, stone, plant, and ground cover, and particle size distribution) and hillslope hydrologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
187
2
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(203 citation statements)
references
References 46 publications
6
187
2
5
Order By: Relevance
“…It has thus been suggested that the relationship between the soil 137 Cs inventory and species diversity (SHDI) can be modulated by the vegetation pattern (LSI) (Bautista et al, 2007). To reveal whether similar vegetation patterns can present the relationship between plant diversity (SHDI) and the extent of soil erosion (soil 137 Cs inventory) better than different patterns (Hou et al, 2014), these plots were divided into nine groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has thus been suggested that the relationship between the soil 137 Cs inventory and species diversity (SHDI) can be modulated by the vegetation pattern (LSI) (Bautista et al, 2007). To reveal whether similar vegetation patterns can present the relationship between plant diversity (SHDI) and the extent of soil erosion (soil 137 Cs inventory) better than different patterns (Hou et al, 2014), these plots were divided into nine groups.…”
Section: Discussionmentioning
confidence: 99%
“…After conducting a study in northeastern Australia, Ludwig et al (2007) suggested that a greater intensity of soil erosion is usually more associated with heterogeneous vegetation patterns rather than homogeneous vegetation patterns. In addition, the relationship between plant diversity and soil erosion can be affected by the vegetation pattern (Bautista et al, 2007). It has been suggested that similar vegetation patterns can be better conditions for determining the relationship between plant diversity and soil erosion than areas with different vegetation patterns (Hou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards banded patterns, the dynamics of spotted vegetation might be more complex, as the former usually act as closed hydrological systems and the latter highly depends on the connectivity of bare areas (Saco et al, 2007). Recent studies demonstrate that it is not only the extent to which vegetation patches prevail on a slope (Parsons et al, 1996;Wainwright et al, 2000;Bochet et al, 2000;Puigdefábregas, 2005) but also the connectivity of bare areas that influences hydrological processes such as runoff and sediment transport (Bautista et al, 2007;Puttock et al, 2013). Connectivity has the advantage, as regards vegetation structure, to provide an explanatory link between abiotic and biotic components to determine the hydrological and ecological function of the system (Turnbull et al, 2008(Turnbull et al, , 2010.…”
Section: Seed Removal By Runoff Influences the Origin Spatial Pattermentioning
confidence: 99%
“…In terms of vegetation patterns, much research focuses on a two-phase mosaic structure of high-and low-vegetation cover patches, which commonly presents itself in semi-arid ecosystems (Pellerin et al 2009;Puigdefabregas 2005;Bromley et al 1997;Cerda 1997;Wilcox et al 2003). Mechanisms of patch formation and dynamics have also been conducted (Mayor et al 2008;Liu et al 2013;Aguiar and Sala 1999;Bautista et al 2007). However, most of these reports and studies focusing on the two-phase vegetation pattern were carried out on degraded land.…”
Section: Introductionmentioning
confidence: 99%